2017
DOI: 10.1021/acs.joc.7b00560
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Transient Zwitterionic Intermediates by N-Acylpyridinium Salts: A Palladium-Catalyzed Diastereoselective Three-Component Reaction

Abstract: We developed a palladium-catalyzed diastereoselective three-component reaction of N-aryl diazoamides, pyridine, and chloroformate, which proceeded through trapping of transient zwitterionic intermediates by in situ formed N-acylpyridinium salts in a regioselective 1,4-addition fashion. This reaction can rapidly provide a library of biologically relevant 4-(2-oxoindolin-3-yl)-1,4-dihydropyridine derivatives in high yields (up to 98%) with moderate to excellent diastereoselectivities (up to >95:5 dr) under mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Recently, the combination of transition metal‐catalyzed formal C−H functionalization of diazo compounds with other chemistry has led to versatile novel synthetic methods [3e,,n–q] . In 2012, Hu and co‐workers reported a Rh(II) and chiral phosphoric acid synergistically catalyzed cascade C−H functionalization/asymmetric imine addition process, furnishing chiral oxindole and indole derivatives [3e] .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the combination of transition metal‐catalyzed formal C−H functionalization of diazo compounds with other chemistry has led to versatile novel synthetic methods [3e,,n–q] . In 2012, Hu and co‐workers reported a Rh(II) and chiral phosphoric acid synergistically catalyzed cascade C−H functionalization/asymmetric imine addition process, furnishing chiral oxindole and indole derivatives [3e] .…”
Section: Methodsmentioning
confidence: 99%
“…The same authors also reported a palladium-catalyzed three-component reaction of pyridine derivatives 1 , chloroformates 364 , and N -aryl diazoamides 365 ( Scheme 171 ). 244 The reaction proceeded through trapping of transient zwitterionic intermediates ( B – C ) by in situ formed N -acylpyridinium salts in a regioselective 1,4-addition fashion, giving access to biologically relevant 4-(2-oxoindolin-3-yl)-1,4-dihydropyridine derivatives 366 in high yields with moderate to very good diastereoselectivities. Different chloroformates efficiently gave the corresponding products.…”
Section: Addition Of Other Nucleophilesmentioning
confidence: 99%
“…In the same year, the same group developed a palladiumcatalyzed dearomative reaction of pyridines in the presence of chloroformate using N-aryl diazoamides as the source of nucleophiles, providing poly-substituted 1,4-dihydropyridine derivatives 83 that contain an oxindole moiety (Scheme 22a). 48 In the postulated mechanism, the palladium catalyst decomposes N-aryl diazoamide 82 to give palladium carbene intermediate 84 in the first step. Then, the zwitterionic intermediate 85 or its enol form 86 is generated from palladium carbene intermediate 84 via intramolecular cyclization.…”
mentioning
confidence: 99%